2016
DOI: 10.1021/acs.est.6b03581
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Significance of Sub-Visible Particles and Colloids in a Submerged Anaerobic Membrane Bioreactor (SAnMBR)

Abstract: The distribution, composition and morphological structure of subvisible particles and colloids (0.01-10 μm) in the supernatant of a lab-scale submerged anaerobic membrane bioreactor (SAnMBR), and their role in membrane fouling, was investigated. Photometric analysis showed that the supernatant and membrane foulants were dominated by particles and colloids (0.45-10 μm), which accounted for over 90% of the total organics (proteins and polysaccharides). Excitation-emission matrix (EEM) fluorescence spectra and mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(25 citation statements)
references
References 64 publications
1
24
0
Order By: Relevance
“…Rather young applications for ultrafiltration of biological suspensions are anaerobic membrane bioreactors [7][8][9] and the recovery of nutrients from manure and anaerobic digestates [10,11]. Anaerobic digestate is a side product of sewage sludge, animal waste, or energy crop fermentation in biogas plants.…”
Section: Introductionmentioning
confidence: 99%
“…Rather young applications for ultrafiltration of biological suspensions are anaerobic membrane bioreactors [7][8][9] and the recovery of nutrients from manure and anaerobic digestates [10,11]. Anaerobic digestate is a side product of sewage sludge, animal waste, or energy crop fermentation in biogas plants.…”
Section: Introductionmentioning
confidence: 99%
“…This further reinforce the idea that the carbohydrates present in wastewater measured using colorimetric assays could be wrongly estimated. The concentration is also in close agreement with other workers, who characterized PS composition in a SAMBR using simple monosaccharide analysis (Zhou et al, 2016).…”
Section: Identification Of Monomeric Structuresupporting
confidence: 91%
“…It may be assumed that, in alkaline conditions there is a general increase in protein-like compounds which can be responsible for fouling the membrane surface. On this topic, Zhou et al (2016) showed that the supernatant and foulants in an AnMBR contains more protein-like compounds compared to polysaccharides at higher operating pH. They also noted that the proteins are more likely to attach to the membrane surface when the ratio of proteins to carbohydrates is as high as 3.1 (Zhou et al, 2016).…”
Section: Membrane Fouling At Different Levels Of Phmentioning
confidence: 99%
“…Research studies have shown that the cake layer formation on membrane surface is aided by an intermediate layer that has a high concentration of carbohydrates. The research performed by Zhou et al (2016) involved photometric analysis showed that the supernatant and membrane foulants in a submerged anaerobic membrane bioreactor (SAnMBR) were dominated by 90% of the total proteins and polysaccharides. At alkaline condition, the rate of initial hydrolysis of organic components is higher compared to the rates in neutral to acidic pH condition (Wang et al, 2019).…”
Section: Membrane Fouling At Different Levels Of Phmentioning
confidence: 99%